THE ROLE OF SOCIAL CAPITAL IN ECONOMIC EMPOWERMENT OF COASTALCOMMUNITIES: A COMPARATIVE LITERATURE STUDY AMONG REGIONS IN INDONESIA - Loso Judijanto; Al-Amin (INJOSEDU: International Journal of Social and Education, 2025)
This research examines the role of social capital in the economic empowerment of coastal communities in various regions in Indonesia through a comparative literature study approach. Social capital, which includes trust, norms and social networks, is believed to have a significant influence on efforts to manage natural resources efficiently and sustainably, increase productivity and reduce poverty in coastal areas. The study found that communities with strong social capital tend to be better able to adapt to climate change and environmental issues, and more easily access development programmes and external assistance. As such, strengthening social capital is an essential strategy for economic empowerment and improving the welfare of coastal communities. These findings emphasise the importance of integrating social capital in sustainable and inclusive development policies for Indonesia's coastal communities.